Service-learning to advance access and success : bridging institutional and community capacity - York, Travis; Tinkler, Alan S., 1965-; Tinkler, Barri E. (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
"In an effort to support these movements, this volume of the Advances in Service-Learning Research series, Service-Learning to Advance Access & Success: Bridging Institutional and Community Capacity, focuses on how service-learning can advance access and success. Not simply access and success of students, but the ways that service-learning can advance access and success for all through bridging institutional and community capacity building. The chapters in this volume serve as a testament to the ways in which service-learning research continue to be advanced by thoughtful scholar-practitioners. The 12 chapters included in this volume are organized into three sections. The first section focuses on how institutional and community partnerships can be leveraged to build community capacity. The second section focuses on how institutions might build their own capacity to effect change for the good of society. The third and final section focuses on six studies exploring the relationship service-learning pedagogy has with access and success for students. Of the six studies, three are situated within the context of teacher-preparation programs"-- Provided by publisher.
Keywords: Service learning -- Case studies.; Community and school -- Case studies.; Education -- Philosophy, Theory & Social Aspects.; Social pedagogy.; Philosophy and theory of education.; elektronické knihy; electronic books